LEJONG TAU, A DIORAMA OF CONFLICT RESOLUTION BASED ON LOCAL WISDOM - Faizal Kurniawan (Jurnal Partisipatoris, 2019)
This study aims to find out in depth the meaning of Lejong that defines "visiting", typical local wisdom of Manggarai. Lejong is convinced as an effort to solve the conflict faced by Manggarai's students in Malang. This research was conducted on some of Manggarai's student communities in Malang, including IKAMMA, IMAMA, and others. This research focused on students who carried out the only Lejong activities, opened in depth about the meaning of Lejong as the local identity of the Manggarai community, especially in conflict management. The results of this study are the existence of local values accepted in the identity of the Manggarai community that has been rooted for a long time ago. It is undoubted that the role of senior in upholding the local identity of the Manggarai community, who are overseas, is also one of the "effective ways" in resolving conflicts that occur between Manggarai's students in Malang. This research is limited only to the Manggarai's students. The hope of this research is to contribute to the study of literature on conflict resolution based on local wisdom.